Modular Product Architecture to Manage Supply Chain Complexity - Ahm Shamsuzzoha (International Journal of Supply Chain Management, 2018)
The aim of this article is to demonstrate and to eliminate or to reduce the complexities associated supply chain management. These complexities are aroused due to the high level of interdependencies between component interfaces and supply chain participants. A case example is presented to define the importance of product architecture with the help of design structure matrix (DSM) tool to reduce product development complexity. To address such complexity this work focuses on the product architecture and supply chain design. This modular principle is elaborated with the objective to reduce the supply chain complexities. The relationship between product architecture and supply chain complexities is defined along with identifying and categorizing various drivers responsible for supply chain complexities.